Co-Seismic Surface Deformation Associated with the 2 May 2025 Padang Panjang Earthquake Derived from Sentinel-1 DInSAR - Khairunnisa, Khairunnisa; Ahadi, Suaidi; Agung Satria, Lori (Journal of the Physical Society of Indonesia, 2026)
This study analyzed surface deformation associated with the Mw 4.8 earthquake that occurred in Padang Panjang, West Sumatra, on May 2, 2025. The purpose of this research was to identify surface changes using Differential Interferometric Synthetic Aperture Radar (DInSAR) with Sentinel-1A imagery from the European Space Agency. The analysis covered the pre-earthquake period (April 8–May 2, 2025) and the post-earthquake period (May 2–June 7, 2025). The deformation values represented displacement along the satellite Line of Sight (LOS). The results showed a clear spatial change between the two periods. Before the earthquake, the area near the epicenter exhibited LOS displacement values of approximately +0.45 mm, while after the earthquake, the values decreased to around −0.045 mm, indicating relative subsidence along the LOS direction. The observed LOS displacement difference of about −0.495 mm suggested a surface response to seismic activity. However, the deformation magnitude was relatively small and may have been influenced by atmospheric effects, decorrelation, and interferometric noise. Therefore, the results were interpreted cautiously without strong tectonic attribution. This study demonstrated the capability of DInSAR to detect subtle surface deformation in seismic regions.